Optimalisasi Sifat Mekanis Kekerasan Ductile Cast Iron Fcd-50 Melalui Proses Heat Treatment - Pratama, Yohanes Juan; Fadhillah, Arief Rizki; Suriansyah, Suriansyah (Widyagama University of Malang, 2024)
At this time the need for metals, especially iron and steel in the industrial world is increasing. One that is widely used is cast iron, there are several types of cast iron, namely gray cast iron, white cast iron, malleable cast iron, nodular cast iron. Nodular cast iron is included in the cast iron class, this type of cast iron is now widely used as a substitute for steel for machine components such as agricultural machinery, automotive, construction and others. For this reason, research was conducted to determine the level of hardness and impact of nodular cast iron (ductile cast iron) FCD-50. In this study, where the hardness test is used as the basis for research to determine the resistance of materials (tensile strength) and changes in the microstructure formed in nodular cast iron (ductile cast iron) FCD-50. This study uses the Heat Treatment method where the cooling process uses oil media. And after the process, a hardness test is carried out. The results of the study obtained were an increase in hardness value from 23.66 HRC to 56.07 HRC. The changes that occurred were greatly influenced by the oil cooling media and holding temperature (holding time) in the isothermal holding pattern.